Towards an Inclusive Digital Cultural Heritage: Frameworks for Representation and Sustainability - Skarzauskiene, Aelita; Mačiulienė , Monika; Kovaitė, Kristina; Šūmakaris, Paulius (European Journal of Sustainable Development, 2025)
The digitisation of cultural heritage (CH) offers significant opportunities for preservation, maintenance, and promotion. However, it also presents challenges in terms of representation and the exhibition of content, particularly for the cultural heritage of minorities. This situation can lead to reduced participation and inclusion of minority groups, creating inequitable representations of diverse values in digitisation efforts and increasing the risk of misuse of digital CH. Existing academic frameworks often inadequately address digitization needs and diverse stakeholder perspectives. There is a need for adaptive frameworks that integrate various values and narratives relevant to digital and multicultural heritage management. The paper emphasizes the need for a more inclusive and collaborative approach to cultural heritage digitization. The proposed Quadruple Helix Ecosystem Framework provides a comprehensive model to guide the development of innovative and sustainable digital heritage initiatives where diverse stakeholders work together to preserve, interpret, and present cultural heritage in the digital age. Keywords: cultural heritage, digitalization, stakeholders, minorities